2012
DOI: 10.1038/ejhg.2012.277
|View full text |Cite
|
Sign up to set email alerts
|

Genes identified in Asian SLE GWASs are also associated with SLE in Caucasian populations

Abstract: Recent genome-wide association studies (GWASs) conducted in Asian populations have identified novel risk loci for systemic lupus erythematosus (SLE). Here, we genotyped 10 single-nucleotide polymorphisms (SNPs) in eight such loci and investigated their disease associations in three independent Caucasian SLE case–control cohorts recruited from Sweden, Finland and the United States. The disease associations of the SNPs in ETS1, IKZF1, LRRC18-WDFY4, RASGRP3, SLC15A4, TNIP1 and 16p11.2 were replicated, whereas no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 30 publications
6
72
0
Order By: Relevance
“…We did not find significant heterogeneity of odds-ratios at most of the risk loci between Asian and European cohorts, consistent with published results (5,42). To understand the contribution of the loci to SLE inheritance, we estimated the percentage of explained heritability of 78 loci (four loci were monomorphic in Asians).…”
Section: à4supporting
confidence: 69%
“…We did not find significant heterogeneity of odds-ratios at most of the risk loci between Asian and European cohorts, consistent with published results (5,42). To understand the contribution of the loci to SLE inheritance, we estimated the percentage of explained heritability of 78 loci (four loci were monomorphic in Asians).…”
Section: à4supporting
confidence: 69%
“…We next asked whether SLC15A4 plays a role in autoantibody production, because SLC15A4 is implicated in the pathogenesis of human SLE (Han et al, 2009;He et al, 2010;Wang et al, 2012). We used a mouse model with a lupus-like disease induced by 2,6,10,14-tetramethylpentadecane (TMPD; also known as pristane) .…”
Section: Slc15a4 Is Required In B Cells For Autoantibody Production Imentioning
confidence: 99%
“…This SLC15A4-dependent pDC function contributes to the pathogenesis of lupus-like disease (Baccala et al, 2013). Genome-wide analyses show that SLC15A4 is closely associated with inflammatory diseases such as type 2 diabetes , systemic lupus erythematosus (SLE) (Han et al, 2009;He et al, 2010;Wang et al, 2012), and inflammatory bowel disease (IBD) (Lee et al, 2009). These observations indicate that SLC15A4 might be a key regulator in autoimmune diseases.…”
Section: Introductionmentioning
confidence: 97%
“…Studies suggest an essential role of Aiolos at later stages of B cell differentiation (61,63). Numerous studies have identified polymorphisms in IKZF1 and IKZF3 to be associated with a risk for development of SLE (64)(65)(66)(67)(68)(69)(70)(71). Thus, modulation of Aiolos and Ikaros expression has the potential to correct multiple aspects of the immune dysregulation mediated by B cells and differentiation into autoantibody-secreting cells associated with SLE.…”
mentioning
confidence: 99%